Waarheid en betekenisgelaagdheid - Toit, D. A. du (Verbum et ecclesia, 2006)
An evaluation of an individual’ s contribution towards theology needs to be placed against the backdrop of the story of faith and theology. In this case it would be the story of religious and theological truth, taking it up in the early Christian Church with the example of the descensus. That showed a plurality of fundamental expressions of faith, as well as a plurality of the forms in which truth is expressed and layered reality of meaning which progressively became unveiled in history. Although this diversity and process was halted by the modern rationalistic intermezzo of the Enlightenment which reduced it to logical, rational and verifiable eternal truths, it gradually reappears in various forms of post-modern thought. It is part of the exciting story of faith and theology in our own time.